Suboptimal Response to Tenofovir Alafenamide in Two Patients With HBeAg-Positive Hepatitis B: A Case Report - Chen, Ruochan; Pei, Siya; Chen, Yayu; Tan, Linxia; Xue, Ying; Liu, Shao; Huang, Yan; Fan, Xuegong (Frontiers in Medicine, 2021)
Tenofovir alafenamide (TAF) is one of the most potent first-line nucleot(s)ide analogs for treating chronic hepatitis B virus (HBV) infections. To date, no cases of TAF drug resistance and/or suboptimal response have been reported. To our knowledge, this is the first report of two adult male patients presenting a suboptimal response response to TAF monotherapy. Our study indicates long-term observations and extensive data are needed to further evaluate the efficacy and safety of TAF, and highlights the need for the development of robust novel direct-acting antivirals and immune therapies for HBV.